Humour in Joel Pett’s Environmental Cartoons on Climate Change - Nemickienė, Živilė; Vengalienė, Dovilė (Technium Education and Humanities, 2024)
The discourse of humour has become a common research topic, but few have analysed the use of humour in environmental cartoons. This study analyses the use of humour in the climate change cartoons of the famous American cartoonist Joel Pett. The analysis explores the verbal and non-verbal means of constructing humour and their interplay. The research was conducted by analysing Joel Pett’s environmental cartoons, examining their content, language and visuals, and identifying the means that enabled the amusing effect. The analysis revealed that the most common verbal means of humour construction in Joel Pett’s climate change cartoons were irony and satire. The study also showed that an interplay between visual and verbal means facilitated humour. In most cases, multimodality, or the interplay between verbal and non-verbal means, was an essential element that allowed the reader to perceive humour. Therefore, it can be suggested that both modes are equally important in the construction of humour in Joel Pett’s environmental cartoons. The results of this study can be used to begin to analyse how humour appears in the work of different environmental cartoonists.